Гармонический анализ дробных обмоток - Дёгтев, Владимир Григорьевич (НТУ "ХПИ", 2013)
Приведены результаты исследования свойств многофазных обмоток объединенного множества включающего в себя обмотки с целыми и дробными числами пазов на полюс и фазу. Разработан алгоритм расчета коэффициентов распределения обмоток указанного множества по гармоникам произвольных порядков. Определено аналитическое соотношение соответствия гармонических составов обмоток, позволяющие представить структуру объединенного множества в виде совокупности гомологических цепочек.

Investigation results for multiphase windings of a united variety that includes windings with fractional and integer number of slots per pole and phase are given. An algorithm of the specified windings distribution coefficients calculation by random orders harmonics is introduced. An analytic ratio of the windings harmonic composition correspondence allowing representing the structure of the united variety as a set of homologous chains is determined.
Fractional windings harmonic analysis
Keywords: дробные обмотки; многофазные обмотки; гомологические цепочки; коэффициент распределения; fractional windings; distribution factor; winding factor; homologous chains; symmetric components method; universal algorithm